Higher Education Language Translation Practices in North Sumatra: Case Study of Lecturer and Student Perceptions - Manik, Kresna Ningsih; Sai Davis, Yong Heng; Nababan, Irene Adryani; Agus Salim Marpaung; Masitowarni Siregar; T. Silvana Sinar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research explores the multifaceted concept of translanguaging in the context of teaching English as a foreign language in three universities in North Sumatra. Translanguaging, a term encompassing various aspects of multilingualism, is examined as a pedagogical approach that utilizes multiple languages within a classroom setting. The study investigates translanguaging practices among lecturers and aims to address three key research questions: the types of translanguaging practices, perceptions of lecturers and students, and the motivations behind incorporating translanguaging in teaching and learning activities. The research method is a qualitative method with a case study approach model focusing on the exploration of a "bounded system" on one specific case or on some cases in detail by exploring data in depth. Through a combination of surveys and interviews with lecturers, the study identifies eight motivations for the intentional use of translanguaging practices. These motivations include adjusting to students' proficiency levels, clarification, and emphasis, translanguaging as an academic strategy, providing challenges for student growth, considering diverse student demographics, expressing firmness and solidarity, addressing real lexical needs in communication, and expressing group identity. The findings reveal positive responses to translanguaging from both lecturers and students, highlighting its versatility in meeting educational objectives and fostering effective communication in diverse learning environments. The motivations align with existing literature, emphasizing the adaptability and significance of translanguaging in enriching the teaching and learning experience. The study concludes with several insights into translanguaging practices in North Sumatra's universities and recommends possibilities for future research and practical implementation. The proposed recommendations include professional development for lecturers, curriculum design, student training, and calls for more studies in tranlanguaging. Overall, this research contributes to the understanding of translanguaging motivations and offers practical suggestions for enhancing its integration in higher education institutions.